ASIC3: A Lactic Acid Sensor for Cardiac Pain - D.C. Immke; E.W. McCleskey (The Scientific World Journal)
Angina, the prototypic vasoocclusive pain, is a radiating chest pain that occurs when heart muscle gets insufficient blood because of coronary artery disease. Other examples of vasoocclusive pain include the acute pain of heart attack and the intermittent pains that accompany sickle cell anemia and peripheral artery disease. All these conditions cause ischemia insufficient oxygen delivery for local metabolic demand — and this releases lactic acid as cells switch to anaerobic metabolism. Recent discoveries demonstrate that sensory neurons innervating the heart are richly endowed with an ion channel that is opened by, and perfectly tuned for, the lactic acid released by muscle ischemia[1,2].